Bahasa inggris: Bahasa indonesia - Fitria, Ruri Yasmina Elisa (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
The subject of this study was a qualitative descriptive study on the students ofSMP PGRI 4 Matesih in 2022. Data collection techniques using data from interviews, observations, and documentation. Interview techniques are intended to obtain data in the form of direct statements from sources, observation techniques are intended to obtain data from participant activities, and documentation techniques are intended to obtain written data and activity photo data. The data analysis technique used is inductive, with 3 paths, namely data reduction, data presentation, and data verification. Judging from the results of the guidance, all participants received good responses and gained an understanding of the importance of responsibility in the school and social spheres. Where participants realize that self-responsibility is very important in daily activities and is not a reason that justifies a process of self-responsibility that is not good. Keywords: Classical Guidance, Self Responsibility